PERAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK DALAM PENANGANAN KASUS KEKERASAN BAGI ANAK KORBAN, PELAKU DAN SAKSI (Studi Kasus Di Kabupaten Pohuwato) - Venty Dwikasari Hasan; Roby W. Amu; Arifin Tumuhulawa (At-Tanwir Law Review, 2023)
This study examines the role of the Integrated Service Center for Women and Children Empowerment (ISCWCE) in handling cases of child violence. The research method used is empirical, using primary data in the form of interviews and primary legal data, secondary legal data and tertiary legal data. The results showed that in carrying out its role, ISCWCE experienced several obstacles, including the lack of assistance personnel in the field which impacted the effectiveness of the services provided and the unavailability of shelter facilities for victims of child violence